Are the sustainable development goals being implemented in the Portuguese higher education formative offer? - Aleixo, Ana Marta (2021)
Purpose: The study aims to examine the vertical integration of the sustainable development goals (SGDs) in Portuguese public higher education institutions, namely, at the level of undergraduate and master’s degrees, and the extent to which Portuguese higher education institutions (HEI) are preparing for the United Nations’ call to promote SDGs. Design/methodology/approach: A content analysis of the designations and objectives of the 2,556 undergraduate and master’s degrees (in 33 Portuguese public higher education institutions) was done to determine whether they promote at least one SDG. Findings: The results show that 198 courses directly address at least one SDG; on average, each higher education institution (HEI) has six courses that explicitly address at least one SDG; universities have more courses in SDG areas than in polytechnics; more master’s degrees embrace SDGs than undergraduate degrees; and most of the courses addressing SDGs are from the social sciences and humanities areas and from natural and environmental sciences. Originality/value: This paper serves to raise the awareness of Portuguese HEIs of their role and responsibility in furthering SGDs.